Heparanase activity expressed by platelets, neutrophils, and lymphoma cells releases active fibroblast growth factor from extracellular matrix. - Ishai-Michaeli, R (1990)
Incubation of platelets, neutrophils, and lymphoma cells with Descemet's membranes of bovine corneas and with the extracellular matrix (ECM) produced by cultured corneal endothelial cells resulted in release of basic fibroblast growth factor (bFGF), which stimulated the proliferation of 3T3 fibroblasts and vascular endothelial cells. Similar requirements were observed for release of endogenous bFGF stored in Descemet's membrane and of exogenous bFGF sequestered by the subendothelial ECM. Release of ECM-resident bFGF by platelets, neutrophils, and lymphoma cells was inhibited by carrageenan lambda, but not by protease inhibitors, in correlation with the inhibition of heparanase activity expressed by these cells. Degradation of the ECM-heparan sulfate side chains by this endo-beta-D-glucuronidase is thought to play an important role in cell invasion, particularly in the extravasation of blood-borne tumor cells and activated cells of the immune system. We propose that both heparanase and ECM-resident bFGF may modulate the cell response to contact with its local environment. Heparanase-mediated release of active bFGF from storage in basement membranes provides a novel mechanism for a localized induction of neovascularization in various normal and pathological processes, such as wound healing, inflammation, and tumor development.